Marketing of development banking innovations in the financial market of Ukraine - Chkan, Iryna; Чкан, Ірина Олександрівна; Trusova, Natalia; Трусова, Наталя Вікторівна; Sakun, Alina (Praha : OKTAN PRINT, 2024)
In the conditions of transformational changes in the economy of the world with a vector for the development of digital innovations in the banking sector and overcoming the crisis of the banking system, an important role is played by effective organization of movement and redistribution of society's resources in monetary terms. Global economic trends demonstrate the objective need to ensure the innovative development of banking institutions as a prerequisite for their survival in a period of financial instability, increasing economic potential.
Keywords: marketing; banking innovations; socio-economic